Impact of Coronary Artery Revascularization Completeness on Outcomes of Patients With Coronary Artery Disease Undergoing Transcatheter Aortic Valve Replacement: A Meta-Analysis of Studies Using the Residual SYNTAX Score (Synergy Between PCI With Taxus and Cardiac Surgery). (March 2018) - Witberg, Guy; Zusman, Oren; Codner, Pablo; Assali, Abid; Kornowski, Ran
Abstract : Background—: Coronary artery disease (CAD) is highly prevalent in patients undergoing transcatheter aortic valve replacement. In the overall CAD population, complete revascularization or reasonable incomplete revascularization (ICR) is associated with improved outcomes; whether the same applies for the transcatheter aortic valve replacement population is still a matter of debate. Methods and Results—: We conducted a systematic review and meta-analysis of studies that examined the prognostic effect of revascularization completeness in patients undergoing transcatheter aortic valve replacement using the residual SYNTAX score (Synergy Between PCI With Taxus and Cardiac Surgery) to separate between reasonable ICR and ICR (using the individual threshold used by each study). Six studies with a total of 3107 patients were included. The duration of follow-up ranged from 0.7 to 3 years. Overall, ICR was associated with an increased risk for mortality. This was true when comparing ICR patients to those with no CAD (odds ratio, 1.85; 95% confidence interval, 1.42–2.40; P <0.01), to those with reasonable ICR (odds ratio, 1.69; 95% confidence interval, 1.26–2.28; P <0.001), or to both groups combined (odds ratio, 1.71; 95% confidence interval, 1.36–2.16; P <0.001). On the contrary, patients in the reasonable ICR category did not show an increased risk for mortality when compared with those with no CAD (odds ratio, 1.11; 95% confidence interval, 0.89–1.39; P =0.33). Conclusions—: Our results suggest that for patients with CAD undergoing transcatheter aortic valve replacement, a residual SYNTAX score–guided revascularization strategy may carry significant benefits in terms of mortality. Adequate revascularization may offer a unique and valuable opportunity to improve the prognosis of these patients. Abstract : Supplemental Digital Content is available in the text.